Collective Memory and Nostalgia in The Dutch Radio2 Top2000 Chart 1999-2013 - Elmer Sterken (Center for Economic Studies and ifo Institute (CESifo), 2014)
The paper analyses the impact of age on the ranking of recorded popular songs in the Dutch Radio2 Top2000 chart in the years 1999-2013. We measure the competition between the loss of collective memory and nostalgia with respect to popular songs. Nostalgic feelings seem to be relevant to recorded songs with an age of 20-40 years. It is shown that the superstar status of the performing artist, the length of the recorded song, and the use of the domestic language (Dutch in our sample) as well as the debut ranking are predictors of the lifespan of a song in the chart.
Keywords: Z11; 330; collective memory; nostalgia; music chart; song age